DOES SULPHUR EXPEL THE COFFEE BERRY BORER FROM Coffea arabica L. FRUITS? - Endo, Ricardo Tsuyoshi; Junior, Salmo de Melo Davi; Silva, Rafael Vinhal; Fernandes, Maria Elisa de Sena; Pereira, Renata Cunha; Teixeira, Adélio Barbosa; Fernandes, Flávio Lemes (Coffee Science - ISSN 1984-3909, 2018)
Technicians and insecticide retailers recommend adding sulfur to the insecticide mixture to expel coffee borer females (Hypothenemus hampei ) from the fruit. The objective in this study was to verify if sulfur expels the coffee borer from the fruit and what the cost associated with the use of sulfur in the insecticide mixture is. Perforated fruits were collected from coffee crops (Red Catuaí, IAC 144) during the granulation phase for the experiments and divided into two lots. The first lot was used to verify the effectiveness of sulfur to expel the borer, and the second to evaluate the effect of temperature x sulfur source x expelling effect on the borer. Sources of sulfur tested were: SK30 and Kumulus DF. The first experiment was the treatments: sulfur sources (two + control without sulfur), two plastic containers (open and closed), five repetitions (factorial: 3 x 2). The second were the treatments: sulfur sources, plastic containers and under two temperatures, factorial 3x2x2. The number of adult females that left the fruits within 24 and 48 h was evaluated. There was no difference in the number of females that abandoned the fruits between treatments with sulfur and control (P> 0.05). It was concluded that sulfur does not expel H. hampei from C. arabica fruits.